2019
DOI: 10.1016/j.ajur.2018.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Albumin-linked prostate-specific antigen-activated thapsigargin- and niclosamide-based molecular grenades targeting the microenvironment in metastatic castration-resistant prostate cancer

Abstract: Localized prostate cancer is curable via annihilation of the entire cancer neighborhood by surgery or local radiation. Unfortunately, once metastatic, no available therapy is curative. The vast majority will die despite aggressive systemic combinational androgen-ablation therapies. Thus, there is an urgent need for effective systemic therapeutics that sterilize the entire microenvironment in metastatic castration-resistant prostate cancer (mCRPC). To accomplish this goal, advantage can be taken of the unique b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 47 publications
0
12
1
Order By: Relevance
“…However, it has been reported that prolonged exposure to thapsigargin can cause stress in the ER and other Ca 2+ stores, and subsequently may evoke the unfolded protein response, caspase activation, mitochondrial release of apoptotic factors, and activation of Ca 2+ ‐dependent endonucleases, eventually resulting in cell death (Foufelle & Fromenty, 2016; Tabas & Ron, 2011). In fact, local SERCA2b inhibition by thapsigargin‐derivates and its effect on Ca 2+ signaling has been recently explored as a potential anti‐cancer therapy (Akinboye, Brennen, Denmeade, & Isaacs, 2019; Doan et al, 2015; Mahalingam et al, 2016). Although SERCA2b is ubiquitously expressed, this strategy relies on local activation of an inactive thapsigargin prodrug in the tumor environment, which may cause death specifically in the cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been reported that prolonged exposure to thapsigargin can cause stress in the ER and other Ca 2+ stores, and subsequently may evoke the unfolded protein response, caspase activation, mitochondrial release of apoptotic factors, and activation of Ca 2+ ‐dependent endonucleases, eventually resulting in cell death (Foufelle & Fromenty, 2016; Tabas & Ron, 2011). In fact, local SERCA2b inhibition by thapsigargin‐derivates and its effect on Ca 2+ signaling has been recently explored as a potential anti‐cancer therapy (Akinboye, Brennen, Denmeade, & Isaacs, 2019; Doan et al, 2015; Mahalingam et al, 2016). Although SERCA2b is ubiquitously expressed, this strategy relies on local activation of an inactive thapsigargin prodrug in the tumor environment, which may cause death specifically in the cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the polar peptide, mipsagargin most likely penetrates cell membranes, causing systemic toxicity in patients [21]. However, a novel and more complex strategy for specific Tg targeting has been introduced and evaluated for possible treatment of metastatic castration-resistant prostate carcinoma [22,23]. This method is based on the coupling of PSA-targeted Tg prodrug via a 2-fluoro-5-maleimidobenzamide linker to human serum albumin (HSA) [23].…”
Section: Introductionmentioning
confidence: 99%
“…However, a novel and more complex strategy for specific Tg targeting has been introduced and evaluated for possible treatment of metastatic castration-resistant prostate carcinoma [22,23]. This method is based on the coupling of PSA-targeted Tg prodrug via a 2-fluoro-5-maleimidobenzamide linker to human serum albumin (HSA) [23]. Coupling to HSA offers favorable properties for the prodrug, such as long half-life in blood, prevention of nonselective permeation into benign cells [1,23], and accumulation in cancer tissue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of novel agents targeting non-AR mechanisms holds great promise to treat PCa that does not respond to AR-targeted therapies. Finally, Dr. John T. Isaacs and colleagues [11] described novel systemic therapeutics that sterilize the entire microenvironment in metastatic CRPC (mCRPC). This novel approach is based on albumin-linked prostate-specific antigen (PSA)-activated thapsigargin- and niclosamide-based molecular grenades targeting the microenvironment in mCRPC.…”
mentioning
confidence: 99%